Identifikasi Bahaya Dan Pengendalian Risiko Sebagai Upaya Mencegah Dan Mengurangi Risiko Kecelakaan Kerja Pada Tambang Batubara Provinsi Kalimantan Timur - Azis, Muh. Heri; Anshariah, Anshariah; Nurwaskito, Arif (Jurnal of Mining Insight, 2023)
Occupational safety and health is a problem that has always been related to the world of work since the beginning of the industrial world began is the emergence of work accidents in their activities that have the potential to cause hazards and work accidents such as property damage, lost time injury to cause fatality . The purpose of this study is to determine the identification of hazards and control the risk of work accidents based on the determination of the risk value of the source of hazard and appropriate control to reduce and eliminate the risk of hazards. The research method carried out is to descriptively describe the situation or object in facts with direct observation. The first thing to do is to find the source of danger using hazard source data, potential hazard data, and K3LH performance report data, then hazard identification and risk assessment based on OHSAS references. Hazards that have been identified are evaluated for risk level. The results of the study found the source of danger that often occurs, namely the concentration of very thick dust and the absence of warning signs. Based on the results of the study, the evaluation carried out is to identify hazards based on the source of hazards obtained in the field and assess and control the source of hazards to reduce the risk of work accidents. From the assessment results, 4 types of risks were obtained, namely four near-miss risks, four property damage risks, three lost time injury risks, and three fatality risks. Conclusions Based on the results of hazard identification and risk control, the hazards that must be prioritized are the risk of fatality and the risk of lost time injury.